The Effect of Price Discount and Promotion on Impulse Buying Through Hedonic Shopping Motivation as An Intervening Variable on Shopee Consumers - Desi Anggarwati; Agus Hermawan; Wening Patmi Rahayu (Badan Penerbit STIEPARI Press, 2023)
The shopee marketplace is a marketing medium that can be used to start an online business, currently many businesspeople are starting to sell through e-commerce and marketplaces. This study aims to determine the effect of price discounts, and promotions on impulse buying through hedonic shopping motivation. This research is a quantitative study using the SPSS 22 program. The population in this study are consumers who shop at the Shopee Marketplace. While the sample in this study was 217 respondents. In addition, to test the feasibility of the instrument, test validity and reliability, test the classical assumptions, and test the hypothesis-with path analysis techniques. The results showed that (1) price discount and promotion support had a direct positive and significant effect on hedonic shopping motivation, (2) price discount support and promotion had a direct positive and significant effect on impulse buying, and (3) hedonic shopping motivation had a direct positive effect and significant effect on impulse buying, (4) price discount support and promotion have a positive and significant indirect effect on impulse buying through hedonic shopping motivation. Based on the results of the study, it is suggested that the shopee marketplace be more selective in maintaining consumer satisfaction to increase the progress of purchasing e-commerce shopee